Crest syndrome and renal involvement - (:unkn) unknown (My University, 2007)
A 66 year-old woman with a history of Raynaud's phenomenon for 30 years, presented with fingertip calcification and ulceration. She complained of discharge of small stones from these ulcerated lesions for several years and dysphagia in the past year. On physical examination, we noticed mild telangiectasias on her face. Calcifications were observed on her foot and hand radiographs. Laboratory findings revealed normal Ca++ and PO4, but the serum parathyroid hormone level was elevated on two occasions. Anticentromer antibody and ANA were positive, whereas anti-ScI 70 was negative. At gastroscopy, esophageal aperistaltism was found and esophagogastroduedonography(EGDG) was suggested. Esophageal dysmotility was found in EGDG and with these findings we decided the patient had CREST syndrome. Hyperparathyroidism was thought to be secondary to calcinosis cutis. We know that during the progression of this disease, the calcinosis type of systemic sclerosis can be characterized by renal involvement and secondary hyperparathyroidism, but it is rarely seen with the CREST syndrome. Because the CREST syndrome is a slowly progressing disease, we believe hyperparathyroidism in this patient developed after many years of hypertension due to the renal disease.
Keywords: CREST syndrome; Hypertension; Renal involvement; Scleroderma